Organizational Culture Change and its Effect on Change Readiness through Organizational Commitment - Suwaryo, Joko; Daryanto, Heny K. K.; Maulana, Agus (UI Scholars Hub, 2016)
In the dynamic global, regional and local environment, organization should be ready to face the challenge of changes. This research aims to understand the relationship between cultural organization, organizational commitment and readiness to change. The research was conducted at Bumiputera 1912 Mutual Life Insurance Company (MLIC) Head Office in August and September 2014 with 190 respondents selected using purposive sampling method. Paired sample t-test and Structural Equation Modeling (SEM) analysis were employed as statistical tools. The results of this study showed that the mean score between existing cultural orientation and preferred cultural orientation differ significantly. SEM analysis found that the existing organizational culture has positive effect on organizational commitment but negatively affects the readiness to change. Preferred organizational culture has a positive effect both on organizational commitment and readiness to change significantly. Organizational commitment has positive effect on readiness to change.